2020
DOI: 10.1111/cns.13463
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound ameliorates depression‐like behaviors in a rat model of chronic unpredictable stress

Abstract: Introduction There is an unmet need for better nonpharmaceutical treatments for depression. Low‐intensity pulsed ultrasound (LIPUS) is a novel type of neuromodulation that could be helpful for depressed patients. Objective The goal of this study was to investigate the feasibility and potential mechanisms of LIPUS in the treatment of depression. Methods Chronic unpredictable stress (CUS) was used to generate rats with depression‐like features that were treated with four weeks of LIPUS stimulation of the ventrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 72 publications
0
21
1
Order By: Relevance
“…LIFUS can normalize the expression of not only inflammatory cytokines (NF-κB, TNF-α, IL-1β) but also downstream signaling proteins such as COX-2 and NF-κB [ 124 ]. In animal studies, LIPUS stimulation of the vmPFC or left PFC improved the rat’s anxiety-depression-like behavior [ 125 , 126 ]. In human studies, Sanguinetti et al found that TUS (2 MHz, 15 s) in the right inferior frontal gyrus increased positive mood for 15–30 min in healthy subjects [ 127 ].…”
Section: Neuromodulation Therapy Reduces Cytokines Production and Imp...mentioning
confidence: 99%
“…LIFUS can normalize the expression of not only inflammatory cytokines (NF-κB, TNF-α, IL-1β) but also downstream signaling proteins such as COX-2 and NF-κB [ 124 ]. In animal studies, LIPUS stimulation of the vmPFC or left PFC improved the rat’s anxiety-depression-like behavior [ 125 , 126 ]. In human studies, Sanguinetti et al found that TUS (2 MHz, 15 s) in the right inferior frontal gyrus increased positive mood for 15–30 min in healthy subjects [ 127 ].…”
Section: Neuromodulation Therapy Reduces Cytokines Production and Imp...mentioning
confidence: 99%
“…It was also shown that chronic, uncontrollable stress contributes to the impairment of the brain stimulation reward system 76 . Therefore, these reports suggest that the chronic stress animal model can be used to study depressive neuropathology, 77 and several studies used this model for the test of therapeutic targets to treat the depressive disorder 78,79 …”
Section: Diverse Animal Models For the Study Of Depressionmentioning
confidence: 99%
“…76 Therefore, these reports suggest that the chronic stress animal model can be used to study depressive neuropathology, 77 and several studies used this model for the test of therapeutic targets to treat the depressive disorder. 78,79 In the mouse model of chronic mild stress, the mice are subjected to unpredictable mild psychosocial stressors for 9 weeks (Figure 2A). 80 From the transcriptome data, many genes showed marked expression changes in brain region including the prefrontal cortex and hippocampus, in chronic mild stress animal models (Table S2).…”
Section: Chronic Mild Stress Modelmentioning
confidence: 99%
“…Additionally, by using chemically deafened mice, it was shown that TUS could decrease the beta band power independent of auditory confound (Wang et al, 2020). To explore the feasibility and potential mechanisms of TUS in depression, ultrasound was applied to the ventromedial prefrontal cortex (vmPFC) of rats and mice with depression-like features (Legrand et al, 2019;Zhang et al, 2021). The chronic unpredictable stress model was used to generate depression-like behaviors, and the vmPFC was chosen because of its role in emotion regulation.…”
Section: Modeling Human Disorders With Animal Modelsmentioning
confidence: 99%